The relative importance of exogenous and substrate‐derived nitrogen for microbial growth during leaf decomposition. Issue 7 (1st July 2013) - Cheever, B. M.; Webster, J. R.; Bilger, E. E.; Thomas, S. A.
Abstract : Heterotrophic microbes colonizing detritus obtain nitrogen (N) for growth by assimilating N from their substrate or immobilizing exogenous inorganic N. Microbial use of these two pools has different implications for N cycling and organic matter decomposition in the face of the global increase in biologically available N. We used sugar maple leaves labeled with 15 N to differentiate between microbial N that had been assimilated from the leaf substrate (enriched with 15 N) or immobilized from the water (natural abundance 15 N: 14 N) in five Appalachian streams ranging in ambient NO3 ‐N concentrations from about 5 to 900 μg NO3 ‐N/L. Ambient NO3 − concentration increased sugar maple decomposition rate but did not influence the proportion of microbial N derived from substrate or exogenous pools. Instead, these proportions were strongly influenced by the percentage of detrital ash‐free dry mass (AFDM) remaining. Substrate‐derived N made up a large proportion of the microbial N after the first 24 h in all streams. Detrital and microbial isotopic 15 N signatures approached that of the water as decomposition progressed in all streams, suggesting that exogenous N may be the predominant source of N for meeting microbial requirements even when exogenous N concentrations are low. Our results support predictions of more rapid decomposition of organic matter in response to increased N availability and highlight the tight coupling of processes driving microbial N cycling and organic matter decomposition.